Multiple lateral sinus pericranii – A case report - Ivetić, Dražen; Pavlićević, Goran; Antić, Branislav; Kostić, Dejan (Vojnosanitetski pregled, 2015)
Introduction. Sinus pericranii is a rare vascular anomaly. It is characterized by abnormal communication between the extracranial and intracranial venous system, usually involving the superior sagittal sinus and occasionally the transverse sinus. Off the midline lesions are extremely rare. Multiplicity, associated venous lakes, venous angioma and lateral location are unusual and unique presentation of sinus pericranii. Case report. A case of multiple congenital off-midline sinus pericranii in the left frontotemporal and parietal region is presented. Magnetic resonance imaging showed an extracranial vascular anomaly connected with the intracranial venous system through abnormal diploic or emissary veins. The lesions were removed completely by surgery. Conclusion. Sinus pericranii is a rare vascular malformation with unique clinical and radiological features. Sinus pericranii may cause fatal complications, and it must be treated by surgical or endovascular procedures.
Keywords: sinus pericranii; neurosurgical procedures; diagnosis; treatment outcome